Critical Success Factors for IT Risk Management in the Digital Transformation Era: Insights from a Multiple Case Study - Yuniarto, Dwi; Rahman, Aedah Binti Abd. (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
The convergence of Information Technology risk management and digital transformation is a vital consideration for contemporary organizations navigating the rapidly changing digital landscape. This research investigates the intersection of these domains, aiming to identify the critical success factors that enable effective Information Technology risk management within the context of digital transformation. Through a Systematic Literature Review, a comprehensive search on Web of Science and Scopus led to the acceptance of 61 peer-reviewed papers published between 2020 and 2024, providing a solid foundation for understanding current trends and best practices. Employing a qualitative multiple case study approach, this study examines the experiences, strategies, and challenges of organizations that have successfully managed Information Technology risks during their digital transformation journeys. Thematic analysis reveals three key critical success factors: executive leadership and support, cross-functional collaboration, and risk-aware decision-making. These findings offer actionable insights for organizations seeking to align their risk management practices with the complexities of digital transformation. By bridging theoretical frameworks with practical insights, this research provides valuable recommendations for organizations to navigate digital transformation securely. Future research could focus on exploring the implementation nuances of these success factors across various industries, such as healthcare, finance, and manufacturing, to deepen our understanding of the intricate relationship between IT risk management and digital transformation in diverse contexts.